2016
DOI: 10.1136/jim-2016-000063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obstructive Sleep Apnea on Ischemia-Modified Albumin Levels and Carotid Intima-Media Thickness

Abstract: Obstructive sleep apnea (OSA) is associated with an increased risk of atherosclerosis. Carotid intima-media thickness (CIMT) is strongly associated with the presence of significant risk factors for cardiovascular disturbances. A disturbance in the oxidative/antioxidative balance is involved in the pathogenesis of OSA and cardiovascular diseases. Ischemia-modified albumin (IMA) is suggested as a novel marker of oxidative stress; IMA can be defined as decreased binding of transitional metal ions to serum albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, its possible role in OSA had not been clearly demonstrated yet. The number of studies focusing on this issue in the literature is limited [10,11,[26][27][28][29]. Yang et al [10] demonstrated a positive correlation between IMA levels and the OSA severity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, its possible role in OSA had not been clearly demonstrated yet. The number of studies focusing on this issue in the literature is limited [10,11,[26][27][28][29]. Yang et al [10] demonstrated a positive correlation between IMA levels and the OSA severity.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding these correlations, they suggested that IMA could be a hypoxemic marker in OSA patients. Karamanli et al [26] stated that serum IMA levels were significantly higher in individuals with OSA compared with the control group with a similar body mass index and age. Sunnetcioglu et al [27] reported that IMA was significantly higher in subjects with OSA and independently associated with severity of OSA defined by AHI and severity of oxygen desaturation.…”
Section: Discussionmentioning
confidence: 98%
“…In the evaluation of IMA levels in OSA patients with CV consequences, carotid intima media thickness has been evaluated, being significantly higher in the OSA group and positively correlated with the AHI and oxygen desaturation index (ODI). These results reflect that IMA, as an oxidative stress biomarker, is related to an increased risk of atherosclerosis production [47].…”
Section: Obstructive Sleep Apnea Biomarkersmentioning
confidence: 62%